2008
DOI: 10.1196/annals.1441.031
|View full text |Cite
|
Sign up to set email alerts
|

Abuse of Amphetamines and Structural Abnormalities in the Brain

Abstract: We review evidence that structural brain abnormalities are associated with abuse of amphetamines. A brief history of amphetamine use/abuse, and evidence for toxicity is followed by a summary of findings from structural magnetic resonance imaging (MRI) studies of human subjects who had abused amphetamines and children who were exposed to amphetamines in utero. Evidence comes from studies that used a variety of techniques that include manual tracing, pattern matching, voxel-based, tensor-based, or cortical thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
242
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(262 citation statements)
references
References 123 publications
(185 reference statements)
11
242
1
5
Order By: Relevance
“…A major study strength is the within-subjects, placebocontrolled design that allowed for participants to serve as their own controls, addressing issues related to the comparison of medication effects across participants that may have differential structural brain changes due to varying histories of methamphetamine use (Berman et al, 2008). Another strength is the investigation of medication-induced alterations in CBF.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…A major study strength is the within-subjects, placebocontrolled design that allowed for participants to serve as their own controls, addressing issues related to the comparison of medication effects across participants that may have differential structural brain changes due to varying histories of methamphetamine use (Berman et al, 2008). Another strength is the investigation of medication-induced alterations in CBF.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…44 There is evidence that prenatal exposure to amphetamines in rodents and humans is associated with abnormal neurological development with lower CNS striatal volumes. 45 As with other vasoconstrictive illicit drugs, an association between amphetamines and gastroschisis has been reported. 15,27 Neonates exposed to amphetamine in utero display increased physiological stress, lethargy and lower arousal in the early postpartum period, 46 and long-term data suggest lower performance at 14 years of age 47 associated with smaller head circumference at birth, although overall follow-up data are limited.…”
Section: Amphetamine/methamphetaminementioning
confidence: 99%
“…In addition, magnetic resonance imaging (MRI) investigations also revealed 3 key changes in the brain structure of MA consumers (4,26); reduction of the gray matter volume in the limbic system and cingulate gyrus, explicit hypertrophy in the white matter of temporal lobe (especially around hippocampus), and reduction of hippocampus volume (27). Some volumetric studies also showed that MA abuse can cause reduction of volume in striatum (28), hippocampus (29), basal ganglia and cerebellum, and increment of cortical gray and white matters of some areas of the brain (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Other MA side effects include cardiovascular disorders, hyperthermia, decreased appetite, insomnia, seizure, epistaxis, extreme weight-loss, nausea, vomiting, severe dental problems (meth mouth), losing teeth, gum disease, stroke, muscle cramps, and tremor (14). Important issue about MA chronic use can remain psychological complications such as depression, anxiety, and paramnesia even after years of pulling out of its use (4,16). Therefore, it seems that MA consumers, compared to abusers of other addictive materials, face more and various psychological disorders (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation